Concrete water towers, bunkers, silos and other elevated structures - Gray,W.S
Concrete water towers, bunkers, silos and other elevated structures / Gray,W.S. -- London: Concrete Pub. Ltd. 624.1834 G778e4 4th ed. No. of Copies : 1